Tabarruk dan Barakah dalam Berbagai Perspektif - Fera Andriani (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2020)
The concept of tabarruk and barakah has been known in the teachings of various groups with diverse terms. Among Muslims themselves there are different points of view in viewing barakah and tabarruk or seeking blessing. This article contains various views on barakah and tabarruk in the perspective of al-Quran and Hadith, views of al-salaf al-salih scholars, and also among the pesantren community, especially traditional ones. Although rationally is not easy to be seen, but with repeated proof, it can be a justification for the existence of barakah itself. With the power of theological and historical roots, the tradition of blessing in this modern era can continue to survive.